2015
DOI: 10.5423/ppj.oa.02.2015.0019
|View full text |Cite
|
Sign up to set email alerts
|

Validation and Application of a Real-time PCR Protocol for the Specific Detection and Quantification of Clavibacter michiganensis subsp. sepedonicus in Potato

Abstract: Clavibacter michiganensis subsp. sepedonicus (Cms) multiplies very rapidly, passing through the vascular strands and into the stems and petioles of a diseased potato. Therefore, the rapid and specific detection of this pathogen is highly important for the effective control of the pathogen. Although several PCR assays have been developed for detection, they cannot afford specific detection of Cms. Therefore, in this study, a computational genome analysis was performed to compare the sequenced genomes of the C. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 38 publications
(48 reference statements)
0
6
0
Order By: Relevance
“…actinidiae (Gallelli et al 2014 ) and Clavibacter michiganensis subsp. sepedonicus (Cho et al 2015 ). The high sensitivity of the developed assay (obtained in our hands) will be invaluable for detecting the target bacteria in the early latent period of the disease, allowing growers to undertake appropriate prevention or protection programmes.…”
Section: Discussionmentioning
confidence: 99%
“…actinidiae (Gallelli et al 2014 ) and Clavibacter michiganensis subsp. sepedonicus (Cho et al 2015 ). The high sensitivity of the developed assay (obtained in our hands) will be invaluable for detecting the target bacteria in the early latent period of the disease, allowing growers to undertake appropriate prevention or protection programmes.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, in the study by Cho et al . 13 , the sensitivity of CMS detection with a real-time PCR method was found to be 5 fg. But according to the CMS detection guide issued by EPPO, the reference method can detect 10 3 –10 4 cell ml −1 CMS, which means at least 10 4 copy DNA, and it is also the typical bacterial load for CMS on potato plants 51 .…”
Section: Discussionmentioning
confidence: 99%
“…Polymerase chain reaction (PCR) is undoubtedly the most commonly used method of DNA-based diagnostic tests 9,10 . PCR methods are used for the detection of CMS in many studies 11–13 . Mills 14 reported that the limit of detection was 100 CFU ml −1 using PCR methods.…”
Section: Introductionmentioning
confidence: 99%
“…Pest distribution outside the EU C. sepedonicus is distributed in Europe, North America and Asia (Figure 1; CABI, 2019; EPPO; 2019). One or more strains from Argentina were included in some studies (Mirza et al, 1993;Fousek et al, 2002;Koko skov a et al, 2005;Cho et al, 2015), but these are likely to be from an interception and the pathogen is not officially reported from that country (CABI, 2019; EPPO, 2019). One or more strains from Argentina were included in some studies (Mirza et al, 1993;Fousek et al, 2002;Koko skov a et al, 2005;Cho et al, 2015), but these are likely to be from an interception and the pathogen is not officially reported from that country (CABI, 2019; EPPO, 2019).…”
Section: 2mentioning
confidence: 99%
“…A finding has been reported in Egypt (Seleim et al, 2014) but not confirmed (EPPO, 2015). One or more strains from Argentina were included in some studies (Mirza et al, 1993;Fousek et al, 2002;Koko skov a et al, 2005;Cho et al, 2015), but these are likely to be from an interception and the pathogen is not officially reported from that country (CABI, 2019;EPPO, 2019). The pathogen was first described in northern Europe and has been traditionally seen as a disease restricted to cool northern temperate countries of the world, but is becoming increasingly widespread (EPPO, 2006;CABI, 2019).…”
Section: 2mentioning
confidence: 99%